3-D strain estimation in sandstone using improved digital volumetric speckle photography algorithm. (May 2021) - Mao, Lingtao; Liu, Haizhou; Wang, Yuwei; Ding, Leilei; Ju, Yang; Chiang, Fu-Pen
Abstract: Accurately and stably estimating the strain in rocks is important to understand their failure mechanism. Digital volumetric speckle photography (DVSP) combined with X-ray computed tomography (CT) has been used to investigate the strain in rocks. This study introduced the inverse compositional Gauss–Newton algorithm into DVSP to improve the accuracy and precision of displacement and strain measurements. Granules with different particle sizes were used to simulate the mesostructure of sandstone, and a series of baseline experiments were conducted to evaluate the accuracy of the improved algorithm, which had a performance that was approximately three times better than DVSP alone. Subsequently, the algorithm was applied to red sandstone subjected to the Brazilian test and an indentation experiment. The interior deformation characteristics of the specimen were clearly depicted, which clarified the failure mechanism of the rock material.